2022
DOI: 10.1097/apo.0000000000000525
|View full text |Cite
|
Sign up to set email alerts
|

Patients Perceptions of Artificial Intelligence in Diabetic Eye Screening

Abstract: Purpose: Artificial intelligence (AI) technology is poised to revolutionize modern delivery of health care services. We set to evaluate the patient perspective of AI use in diabetic retinal screening. Design: Survey. Methods: Four hundred thirty-eight patients undergoing diabetic retinal screening across New Zealand participated in a survey about their opinion of AI technology in retinal screening. The survey consisted of 13 questions covering topics of awareness, trust, and receptivity toward AI systems. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Previously we have demonstrated that it is possible to train an artificial intelligence (AI) deep learning (DL) algorithm on retinal images to grade diabetic retinopathy and maculopathy for diagnostic, screening and risk assessment purposes [30,[36][37][38][39][40][41][42][43][44][45]. In this study we used 110,272 fundus images from a database of 55,118 patients from the UK Biobank and AREDS 1 datasets to train and subsequently test a novel AI platform (CVD-AI) to calculate a 10-year CVD risk score for these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Previously we have demonstrated that it is possible to train an artificial intelligence (AI) deep learning (DL) algorithm on retinal images to grade diabetic retinopathy and maculopathy for diagnostic, screening and risk assessment purposes [30,[36][37][38][39][40][41][42][43][44][45]. In this study we used 110,272 fundus images from a database of 55,118 patients from the UK Biobank and AREDS 1 datasets to train and subsequently test a novel AI platform (CVD-AI) to calculate a 10-year CVD risk score for these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, DL architectures are used for learning to recognize a variety of eye-related diseases in ophthalmology to improve diagnosis rates with clinically acceptable performance, compared to ophthalmology specialists [ 6 ]. Thus, AI could effectively serve as a reliable safety platform for both patients and doctors, and as an auxiliary tool to promptly judge the results; this could not only reduce the possibility of misdiagnosis, but could also improve patient experience by expediting efficient treatment [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding patients' attitudes is crucial for the successful integration of artificial intelligence (AI) in healthcare, but patients' perceptions on this matter have been seldom studied. [1][2][3][4] As AI is currently applied for diabetic retinopathy (DR) screening, our objective was to evaluate patients' perceptions on AI during a DR screening event.…”
mentioning
confidence: 99%
“…Nevertheless, by collecting answers on-site, during an actual (as opposed to hypothetical) situation, and reporting patients' perspectives on AI, we believe our research brings robust and original information and helps shedding light onto this very important but often neglected stakeholder. [1][2][3] The answers were given in the realm of a specific application, as opposed to a general approach of AI in health. 1 While only 14% reported good or expert knowledge in AI, most had positive views of AI in health but prefer a cooperation of AI and human physicians, in line with other reports.…”
mentioning
confidence: 99%
See 1 more Smart Citation